Mirror Neurons System Engagement in Late Adolescents and Adults While Viewing Emotional Gestures - Salvia, Emilie; Süß, Moritz; Tivadar, Ruxandra; Harkness, Sarah; Grosbras, Marie-Hélène (Frontiers in Psychology, 2016)
Observing others’ actions enhances muscle-specific cortico-spinal excitability, reflecting putative mirror neurons activity. The exposure to emotional stimuli also modulates cortico-spinal excitability. We investigated how those two phenomena might interact when they are combined, i.e. while observing a gesture performed with an emotion, and whether they change during the transition between adolescence and adulthood, a period of social and brain maturation. We delivered single-pulse transcranial magnetic stimulation (TMS) over the hand area of the left primary motor cortex of 27 healthy adults and adolescents and recorded their right first dorsal interossus (FDI) muscle activity (i.e. motor evoked potential – MEP), while they viewed either videos of neutral or angry hand actions and facial expressions, or neutral objects as a control condition. We reproduced the motor resonance and the emotion effects -- hand-actions and emotional stimuli induced greater cortico-spinal excitability than the faces / control condition and neutral videos, respectively. Moreover, the influence of emotion was present for faces but not for hand actions, indicating that the motor resonance and the emotion effect might be non-additive. While motor resonance was observed in both groups, the emotion effect was present only in adults and not in adolescents. We discuss the possible neural bases of these findings.